Smart Clothing with Built‐In Soft Sensing Network for Measuring Temporal and Spatial Distribution of Pressure under Impact Scenarios (Adv. Sensor Res. 2/2023). Issue 2 (10th February 2023) - Wang, Fei; Zhu, Bo; Shu, Lin; Li, Ying; Lai, Xinghua; Ma, Lingchen; Ji, Peijun; Zhou, Qing; Yu, Tongxi; Tao, Xiaoming
Abstract : Soft Pressure Sensor In article number 2200019, Xiaoming Tao and co‐workers use, for the first time, smart clothing designed with soft pressure sensing network to acquire the in‐situ and quantitative values of pressure distribution between the seat belts, seat cushion, and the dummy in a standard sled crash test.